2013
DOI: 10.1074/jbc.m113.505735
|View full text |Cite
|
Sign up to set email alerts
|

Glycerophosphocholine Utilization by Candida albicans

Abstract: Background: Glycerophosphocholine (GroPCho) is a phospholipid metabolite found throughout the human body. Results: Loss of Git3 and Git4 in C. albicans abolishes GroPCho transport, and Git3-deficient cells exhibit reduced virulence. Conclusion: The major GroPCho transporter, Git3, is required for full virulence. Significance: This report is the first to identify a eukaryotic GroPCho-specific transporter and the first to implicate GroPCho utilization in pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 60 publications
1
42
0
Order By: Relevance
“…data 3). Indeed, it has been shown that the ability of C. albicans to utilize external glycero-phosphocholine is important for virulence in murine systemic candidiasis29 and that RHR2 is essential for proliferation of C. albicans in the liver of intraperitoneally infected mice30.…”
Section: Resultsmentioning
confidence: 99%
“…data 3). Indeed, it has been shown that the ability of C. albicans to utilize external glycero-phosphocholine is important for virulence in murine systemic candidiasis29 and that RHR2 is essential for proliferation of C. albicans in the liver of intraperitoneally infected mice30.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that GPC is believed to only be formed via deacylation of PC, and if so, GPCAT cannot contribute to any net synthesis of PC if GPC is not provided to the cell from outside. Because plasma membrane GPC transporters are found in yeast (5, 17) and fungi (18), exogenous GPC could, however, under certain environmental conditions contribute to net synthesis of PC via GPCAT in these cells. In all cells, GPCATs would contribute to an acyl editing, whereby acyl groups from the acyl-CoA pool can be inserted into the s n -1 position of PC via LPC formation from GPC.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted/periplasmic form of Plb1 is most likely responsible for the production of extracellular GroPCho. Notably, extracellular GroPCho is not a dead end metabolite but can be recycled into PC synthesis following its uptake via glycerophosphodiester transporters that have been identified in both S. cerevisiae (74) and Candida albicans (46,75).…”
Section: Discussionmentioning
confidence: 99%